How S100B crosses brain barriers and why it is considered a peripheral marker of brain injury - Gayger-Dias, Vitor; Vizuete, Adriana F.K.; Rodrigues, Letícia; Wartchow, Krista Minéia; Bobermin, Larissa; Leite, Marina Concli; Quincozes-Santos, André; Kleindienst, Andrea; Gonçalves, Carlos Alberto (Experimental Biology and Medicine, 2023)
S100B is a 21-kDa protein that is produced and secreted by astrocytes and widely used as a marker of brain injury in clinical and experimental studies. The majority of these studies are based on measurements in blood serum, assuming an associated increase in cerebrospinal fluid and a rupture of the blood–brain barrier (BBB). Moreover, extracerebral sources of S100B are often underestimated. Herein, we will review these interpretations and discuss the routes by which S100B, produced by astrocytes, reaches the circulatory system. We discuss the concept of S100B as an alarmin and its dual activity as an inflammatory and neurotrophic molecule. Furthermore, we emphasize the lack of data supporting the idea that S100B acts as a marker of BBB rupture, and the need to include the glymphatic system in the interpretations of serum changes of S100B. The review is also dedicated to valorizing extracerebral sources of S100B, particularly adipocytes. Furthermore, S100B per se may have direct and indirect modulating roles in brain barriers: on the tight junctions that regulate paracellular transport; on the expression of its receptor, RAGE, which is involved in transcellular protein transport; and on aquaporin-4, a key protein in the glymphatic system that is responsible for the clearance of extracellular proteins from the central nervous system. We hope that the data on S100B, discussed here, will be useful and that it will translate into further health benefits in medical practice.
CRIS-Team Scopus Importer:2023-12-22
Keywords: AQP-4; Astrocyte; BBB; glymphatic system; RAGE; S100B; tight junctions